Hubungan Aspek Dukungan Sosial Keluarga terhadap Tekanan Darah Terkontrol pada Lansia dengan Hipertensi - Farach Aliffatunisa; Noor Rochmah Ida Ayu Trisno Putri; Feti Kumala Dewi; Ita Apriliyani (Poltekkes Kemenkes Bengkulu, 2021)
Life Expectancy (UHH) in Indonesia has increased which makes the number of elderly people high, thereby increasing the burden of non-productive age on productive age related to problems that can occur in the elderly. One of them is hypertension where the elderly have a risk level of 2.18 times in the elderly aged 60-64 years. Hypertension treatment is carried out continuously so that support from the family is needed to achieve a controlled pressure value to avoid complications considering the weakening ability of the elderly. This study aims to analyze the relationship between aspects of family social support and controlled blood pressure in the elderly with hypertension. The design of this study was cross sectional with purposive sampling so that 42 elderly people were obtained according to the inclusion and exclusion criteria. The research instrument used the Widiawati Adoption Family Support Questionnaire (2016). The results of the analysis using Spearman Rank showed that there was a relationship between aspects of family social support and controlled blood pressure in the elderly with hypertension (r=0.598**; p=0.000). Family support affects blood pressure control so that it is expected that the family will provide optimal support.